2012
DOI: 10.1016/j.cell.2012.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing Chromosomal Abnormalities Reveals Neurodevelopmental Loci that Confer Risk across Diagnostic Boundaries

Abstract: SUMMARY Balanced chromosomal abnormalities (BCAs) represent a reservoir of single gene disruptions in neurodevelopmental disorders (NDD). We sequenced BCAs in autism and related NDDs, revealing disruption of 33 loci in four general categories: 1) genes associated with abnormal neurodevelopment (e.g., AUTS2, FOXP1, CDKL5), 2) single gene contributors to microdeletion syndromes (MBD5, SATB2, EHMT1, SNURF-SNRPN), 3) novel risk loci (e.g., CHD8, KIRREL3, ZNF507), and 4) genes associated with later onset psychiatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
515
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 542 publications
(539 citation statements)
references
References 122 publications
21
515
0
3
Order By: Relevance
“…30,32,34,38 Our results are consistent with this observation as patients 3 and 4 with duplication of exon 5 have ASDs. Both these duplications are not expected to alter the reading frame, but can result in addition of amino-acid residues to the amino terminus of the protein.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…30,32,34,38 Our results are consistent with this observation as patients 3 and 4 with duplication of exon 5 have ASDs. Both these duplications are not expected to alter the reading frame, but can result in addition of amino-acid residues to the amino terminus of the protein.…”
Section: Discussionsupporting
confidence: 90%
“…25 Haploinsufficiency of AUTS2 (three reports of apparently balanced translocation and two reports of inversion) has been associated with ASDs, ID, seizures, and attention deficit hyperactivity disorder. [26][27][28][29][30][31]34 Sultana et al 30 reported monozygotic twins with ID and autism with an apparently balanced t(7;20) (q11.2; p11.2) that disrupted AUTS2. Kalscheuer et al 32 described translocations involving AUTS2 in three unrelated individuals with mild to moderate ID.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies of simplex families using microarrays with greater resolution found a burden rate of de novo CNVs from 5.8-7.9% in probands to 1.7-2.0% in unaffected siblings [97,98]. Furthermore, an increased CNV burden was identified in the same loci encompassing balanced chromosomal abnormalities, such as translocations and inversions, in an autism/neurodevelopmental disorder cohort [99].…”
Section: Cnvs In Asdmentioning
confidence: 99%